Exploring students’ emotional state during a test-related task using wearable electroencephalogram - Yeison Alberto Garces-Gomez; Ruben Darío Lara-Escobar; Paula Andrea López-Jimenez; Nicolás Toro-García; Jose Israel Cardenas-Jimenez; Carlos Augusto Gonzalez-Correa; Clara Helena Gonzalez-Correa (Institute of Advanced Engineering and Science, 2023)
Using wireless sensors for brain activity, brain signals associated with the mood states of engineering students have been captured before and during the taking of a mathematics exam. The characterization of brain lobule activity related to arousal/valence states was analyzed from reports on the literature of the horizontal dimensions of pleasure-displeasure and vertical dimensions representing arousal-sleep. The results showed a direct relationship of the level of students’ arousal with the event of taking an exam as well as feelings of negative emotions during the exam presentation. The development of this research can lead to the implementation of controlled spaces for the presentation of students’ exams in which arousal/valence states can be controlled so that they do not affect their performance and the fulfillment of the goals, achievements or objectives established in a program or subject.